2019
DOI: 10.3390/v11121086
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nuclear Localization Signals in the ORF2 Protein of Porcine Circovirus Type 3

Abstract: Porcine circovirus type 3 (PCV3) contains two major open reading frames (ORFs) and the ORF2 gene encodes the major structural capsid protein. In this study, nuclear localization of ORF2 was demonstrated by fluorescence observation and subcellular fractionation assays in ORF2-transfected PK-15 cells. The subcellular localization of truncated ORF2 indicated that the 38 N-terminal amino acids were responsible for the nuclear localization of ORF2. The truncated and site-directed mutagenesis of this domain were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…NPM1 has been demonstrated to interact with PCV2 Cap protein and contribute to PCV2 replication ( Zhou et al, 2020 ). As reported in previous studies, in which PCV3 Cap was found to have a nucleolar localization signal ( Mou et al, 2019 ), the present study also demonstrated that PCV3 Cap interacts and colocalizes with nucleolar phosphoprotein NPM1 ( Zhou et al, 2021 ). Thus, we focused on the interaction between the PCV3 Cap protein and NPM1 and the contribution of NPM1 to PCV3 replication in subsequent experiments.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…NPM1 has been demonstrated to interact with PCV2 Cap protein and contribute to PCV2 replication ( Zhou et al, 2020 ). As reported in previous studies, in which PCV3 Cap was found to have a nucleolar localization signal ( Mou et al, 2019 ), the present study also demonstrated that PCV3 Cap interacts and colocalizes with nucleolar phosphoprotein NPM1 ( Zhou et al, 2021 ). Thus, we focused on the interaction between the PCV3 Cap protein and NPM1 and the contribution of NPM1 to PCV3 replication in subsequent experiments.…”
Section: Resultssupporting
confidence: 90%
“…Without encoding DNA polymerase in circoviruses, the replication machinery of the host cell is needed for de novo DNA synthesis ( Heath et al, 2006 ). All PCVs possess a nuclear localization signal (NLS) at the N-terminus of the Cap protein ( Liu et al, 2001 ; Shuai et al, 2008 ; Mou et al, 2019 ). Although the amino acids of the PCV3 Cap protein are significantly different from those of PCV1 and PCV2, their motifs within the NLSs share some similarities ( Liu et al, 2001 ; Shuai et al, 2008 ; Mou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of the putative Cap, a nuclear localization signal (NLS) was predicted in the N-terminus of the putative Cap of E115 strain (Figure 4). Based on the alignment with other members of Circovirus genus, Figure 4 showed that the arginine-rich region of E115 strain was aligned with the basic motifs of the experimentally confirmed NLS of PCV1, PCV2 and PCV3 (Liu, Tikoo, & Babiuk, 2001;Mou, Wang, Pan, & Chen, 2019;Shuai et al, 2008). Additionally, motif screening (Figure 5) indicated that the putative Cap of E115 strain contained several tyrosine-based Y-x-x-φ motifs and P-x-x-P motifs (x represents any amino acid and φ denotes a large hydrophobic residue of either F, I, L or V) which were related to clathrin-mediated endocytosis (Sobhy, 2016).…”
Section: Genome Organization and Viral Proteins Functional Analysismentioning
confidence: 99%
“…The ORF2-encoded capsid protein (Cap) is necessary for virion packaging and participates in genome replication by interacting with Rep protein and is also the main viral immunogen and acts as a key regulator of viral replication as well as the virus-host interaction [27][28][29][30][31][32][33][34]. The N-terminus of PCV3 Cap is rich in basic amino acids, and the amino acid residues 1-34 was identified as nuclear localization signal (NLS), which is essential for nuclear transport of PCV3 Cap [35]. Besides, PCV3 Cap interacts with signal transducer and activator of transcription 2 (STAT2) to inhibit type I interferon signaling [36].…”
Section: Introductionmentioning
confidence: 99%